2018
DOI: 10.1016/j.talanta.2018.02.110
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a handheld near infrared device for the qualitative analysis of bloodstains

Abstract: One of the most common tasks in criminal investigation is to determine from which tissue source a biological fluid stain originates. As a result, there are many tests that are frequently used to determine if a stain is blood, semen or saliva by exploiting the properties of certain molecules present within the fluids themselves. These include chemical reagents such as the Kastle-Meyer or Acid Phosphatase tests, as well as other techniques like the use of alternative light sources. However, most of the tests cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Interestingly, it was shown recently that miniaturized NIR spectroscopy was capable of analyzing blood stains, [97, 98] and that the sensitivity of the method did not seem to present a major issue. This shows the potential for NIR spectroscopy to compete with IR or Raman techniques, which are already in use for such purposes [99–102] …”
Section: Miniaturized Nir Spectroscopy In Practical Applicationsmentioning
confidence: 99%
“…Interestingly, it was shown recently that miniaturized NIR spectroscopy was capable of analyzing blood stains, [97, 98] and that the sensitivity of the method did not seem to present a major issue. This shows the potential for NIR spectroscopy to compete with IR or Raman techniques, which are already in use for such purposes [99–102] …”
Section: Miniaturized Nir Spectroscopy In Practical Applicationsmentioning
confidence: 99%
“…Two studies 213,214 have used portable NIR spectrometers and supervised pattern recognition methods for discrimination and confirmatory identification of bloodstains in different substrates. In the first, Pereira et al 213 analyzed dried human and animal bloodstains and several red-colored products that could be commonly perceived as blood, such as red lipstick, pepper sauce, soy sauce, red wine and balsamic vinegar.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…PLS-DA correctly classified human blood and other stains in all substrates. Morillas et al 214 analyzed bloodstains and eight other substances that resembled fresh or dry blood, such as red wine, red ink, tomato sauce, fake blood, coffee, red food coloring, red paint and beet root juice. The substrates used were glass slides, tile, wood, 100% leather, 100% acrylic and 100% cotton.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…Morillas et al used a portable NIR spectrometer for bloodstain identification. The authors observed good results with 81–94% accuracy with different classification models [ 22 ].…”
Section: Introductionmentioning
confidence: 99%